2016
DOI: 10.1093/jmcb/mjw002
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang 1 promotes mTORC2-mediated AKT phosphorylation

Abstract: Yin Yang 1 (YY1) regulates both gene expression and protein modifications, and has shown a proliferative role in cancers. In this study, we demonstrate that YY1 promotes AKT phosphorylation at S473, a marker of AKT activation. YY1 expression positively correlated with AKT(S473) phosphorylation in a tissue microarray and cultured cells of breast cancer, but negatively associated with the distant metastasis-free survival of 166 breast cancer patients. YY1 promotes AKT phosphorylation at S473 through direct inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…Our results also showed that YY1 was directly targeted by miR‐141‐3p, and ectopic expression of YY1 reversed the anti‐cancer activity of miR‐141‐3p, further supporting that YY1 functions as an oncogene in thyroid cancer. Furthermore, the downstream targets of YY1, including p53 , Snail , Myc , Fos , ERBB2 , and RKIP have been directly implicated in cancer progression (Gordon et al, ; Zhang et al, ). YY1 also regulates additional targets involved in cell proliferation and apoptosis, including EZH2, Mdm2, caspases, and HDACs (Gordon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that YY1 was directly targeted by miR‐141‐3p, and ectopic expression of YY1 reversed the anti‐cancer activity of miR‐141‐3p, further supporting that YY1 functions as an oncogene in thyroid cancer. Furthermore, the downstream targets of YY1, including p53 , Snail , Myc , Fos , ERBB2 , and RKIP have been directly implicated in cancer progression (Gordon et al, ; Zhang et al, ). YY1 also regulates additional targets involved in cell proliferation and apoptosis, including EZH2, Mdm2, caspases, and HDACs (Gordon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…AKT activation can also be regulated by Yin Yang 1 (YY1) 23 . YY1, a transcription factor, can either activate 24 , 25 or repress 26 , 27 the expression of genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expression and function of YY1 in HNSCC remain to be explored. YY1 also directly interacts with several important cancer-related regulators including AKT 23 . Moreover, overexpression of YY1 confers cancer cells with resistance in chemotherapies 36 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, using cysteine mutagenesis, we discovered that ZF2 and ZF3 play an essential role in YY1-mediated transcription and cell proliferation. In addition, although multiple reports, including ours [12,13,15], revealed YY1 regulatory properties independent of its transcriptional activity, our current study unequivocally demonstrated that YY1-mediated gene expression through ZF binding to DNA is crucial and indispensable to its biological function.…”
Section: Discussionmentioning
confidence: 40%
“…YY1 can exert its function through mechanisms either dependent or independent of its transcriptional activity. We previously reported that YY1 could negatively regulate the expression of p53 and p27, and promote phosphorylation and activation of AKT [12,13,15]. Other groups reported YY1 could activate expression of many oncogenes, including MYC, ERBB2, and COX-2 [16][17][18].…”
mentioning
confidence: 99%